GROWTH AND REPRODUCTION OF GELIDIELLA ACEROSA IN THE PALK BAY AND GULF OF MANNAR NEAR MANDAPAM - Rao, M Umamaheswara (Indian Journal of Fisheries, 2011)
Studies on growth and reiMrodusticn of Gelidiella acerosa growing in the PalkBay near Ramsswaram and in the Gulf of Mannar near Pudumadam, have been carriedout for three yeais from 1968 to 1970. Results obtained show that the plants of Ge/i-(/ie//(ti(icera.sa, which occur throughout the year, attain max •mum size in two seasonswith a half yearly gruwth cycle and that the main growth season varies in the Palk Bayand Gulf of Mannar. The main growth season with peak number of large size frondswasfoundbetweenE>ecember and April on the Palk Bay side and between July andAugust on the Gulf of Mannar side. The fruiting cycle of Gelidiella aceroia extendsfor a period of 7 to 9 months in a year and maximum nimiber of tetrasporic plants occurin the population jus t afteir the two peak growth periods. Considering the local changesin growth bshaviour, slow growth rate and the fruiting cycle, the period frcm Decemberto April was found to be suitable for collecting Gelidiella acerosa in the Falk Bay andfrom July to August/September in the Gulf of Mannar.